IMPLEMENTATION OF THE HYPERTENSION PREVENTETION PROGRAM THROUGH HYPERTENSION EXERCISE FOR THE ELDERLY AT WISMA CEMPAKA UPT PSTW PUGER JEMBER REGENCY - Yusuf Afandi; Dhea Cristina; Nadhea Alfionita; Siti Sholikah; Tantut Susanto (UNUSA Press, 2022)
Hypertension is increased blood pressure in the arteries continuously over a period, where the symptoms of hypertension are very diverse in each individual. Hypertension is a systolic and diastolic pressure of more than 160mmHg and 90mmHg, which is also common in the elderly. Objective: This study aims to determine the impact of providing health education related to hypertension and anti-hypertensive exercise on blood pressure in the elderly at Wisma Cempaka UPT PSTW Jember. This research used a quasi-experimental pre-test and post-test one-group design. The sampling technique used is a total sampling of 16 respondents. Data collection techniques were simple interviews, questionnaires and measuring blood pressure using a sphygmomanometer. Data were analyzed using the T-Test. The implementation includes health education, and blood pressure measurement, hypertension exercise. The results of statistical tests showed that there was an effect on blood pressure results before and after the Hypertension exercise. The respondent's blood pressure in the pre-test obtained average systolic 128.75 mmHg, and average diastolic pre-test 80.94 mmHg. The average post-test systolic value is 119.38 mmHg, and the average post-test diastolic is 77.19 mmHg. The level of knowledge of the elderly at Wisma Cempaka has increased with changes in post-test scores. This result proves the importance of health education and hypertension exercise in controlling blood pressure. There is a difference in systolic blood pressure before and after anti-hypertensive exercise. Anti-hypertensive exercise can be used as an alternative modification to lower blood pressure in the elderly with hypertension and provide health education for knowledge of controlling blood pressure.